Cardiovascular Hyperreactivity as a Predictor of Hypertension in Women - Milagros Lisset León Regal; Mikhail Benet Rodríguez; Luís Alberto Mass Sosa; Sandra Willians Serrano; Lázaro Hermes González Otero; Alain León Valdés (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2016)
Background: there is insufficient evidence to state that cardiovascular hyperreactivity is a predictive risk factor for hypertension in women. Objective: to determine the predictive value of cardiovascular hyperreactivity for hypertension in women. Methods: a prospective cohort study was conducted in 212 women: 120 normoreactive and 92 hyperreactive. Two measurements were performed, one in 2004 to identify the presence or absence of cardiovascular reactivity, and another in 2009 to detect high blood pressure through the hand-held weight test. The variables studied included cardiovascular hyperreactivity, obesity, age, family history of hypertension, and smoking. The relative risk of developing high blood pressure in hyperreactive women was determined by using a logistic regression model. Results: the incidence of hypertension after five years was three times higher in hyperreactive women than in the normoreactive. Cardiovascular hyperreactivity was the most significant variable for predicting hypertension. Conclusion: women with cardiovascular hyperreactivity carry a higher risk of developing hypertension than normoreactive ones. Cardiovascular hyperreactivity is the risk factor that showed the highest predictive value for hypertension.